2019
DOI: 10.1039/c9tc03936h
|View full text |Cite
|
Sign up to set email alerts
|

An emerging Janus MoSeTe material for potential applications in optoelectronic devices

Abstract: Motivated by the extraordinary physical and chemical properties of Janus transition-metal dichalcogenides (TMDs) due to the change of the crystal field originating from their asymmetry structures, the electronic and optical properties of the MoSeTe monolayer in 2H and 1T phases are systematically studied by first-principles calculations, and a detailed comparison with the parental MoSe2 and MoTe2 monolayer is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 60 publications
3
48
1
Order By: Relevance
“…The new family of 2D materials named Janus transition metal chalcogenides (TMDs) monolayer has been recently synthesized [ 32 , 33 ]. Due to the asymmetry sandwich combinations (i.e., X-M-Y, where M = transition element, X, Y = chalcogen atoms but X ≠ Y) of Janus TMDs monolayer have very interesting physical and chemical properties [ 34 , 35 , 36 , 37 , 38 , 39 ]. Additionally, due to the quite different atomic radius and electronegativities of X and Y atoms, the charge distributions of the layer X-M and M-Y in Janus monolayer are significantly different [ 34 , 35 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new family of 2D materials named Janus transition metal chalcogenides (TMDs) monolayer has been recently synthesized [ 32 , 33 ]. Due to the asymmetry sandwich combinations (i.e., X-M-Y, where M = transition element, X, Y = chalcogen atoms but X ≠ Y) of Janus TMDs monolayer have very interesting physical and chemical properties [ 34 , 35 , 36 , 37 , 38 , 39 ]. Additionally, due to the quite different atomic radius and electronegativities of X and Y atoms, the charge distributions of the layer X-M and M-Y in Janus monolayer are significantly different [ 34 , 35 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the asymmetry sandwich combinations (i.e., X-M-Y, where M = transition element, X, Y = chalcogen atoms but X ≠ Y) of Janus TMDs monolayer have very interesting physical and chemical properties [ 34 , 35 , 36 , 37 , 38 , 39 ]. Additionally, due to the quite different atomic radius and electronegativities of X and Y atoms, the charge distributions of the layer X-M and M-Y in Janus monolayer are significantly different [ 34 , 35 , 40 ]. As a consequence, Janus MXY monolayer generates interior electric fields transverse to the surface [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion energy correction was considered using the DFT-D3 method by Grimme et al 55 , 56 In addition, many previous studies have reported that the spin–orbit coupling (SOC) interaction plays an important role in the 2D TMD monolayers. 39 , 57 59 Hence, we have included the spin–orbit coupling (SOC) interaction in the calculations. 60 …”
Section: Computational Detailsmentioning
confidence: 99%
“…12(d-f)) in the IR region of the spectrum for all the stretched penta-MP 2 compounds suggest that these compounds will not absorb much heat, and they can be used as good hot mirrors for application in heat control, environmental protection, coatings, etc. [83][84][85] For the sake of completeness, we also calculated the optical properties of the penta-MP 2 (M ¼ Ni, Pd and Pt) monolayers without strain, as presented in Fig. S8 (ESI †), for comparison.…”
Section: Nanoscale Advances Papermentioning
confidence: 99%